2022
DOI: 10.1002/ldr.4310
|View full text |Cite
|
Sign up to set email alerts
|

The impact of stress factors on riparian and drawdown zones degradation around dams and reservoirs

Abstract: There is currently a lack of evidence about changes in the health of riparian and drawdown zones under different land‐use patterns within mega‐reservoirs, below and around dams. Scientific evidence for the quantitative effects of stress indicators is vague and varies significantly among reservoirs and dams worldwide. In this study, we used a field‐based approach to evaluate riparian and drawdown zones health changes—influenced by pressure indicators—across 274 transects from three land‐use areas (rural, rural–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 68 publications
(134 reference statements)
2
13
0
Order By: Relevance
“…The TGDR is the largest reservoir in China, located between Jiangjin in Chongqing and Yichang in Hubei, with an area of 349 km 2 . The TGDR implements a hydrological dispatching model of winter storage and summer discharge, creating a hydro-fluctuation zone with a water level difference of up to 30 m during 1 year (Sang et al, 2019 ; Arif et al, 2022b ). The site is part of the subtropical southeast monsoon region's mountainous climate, with an average annual accumulated temperature of 18.2°C, long sunshine hours, sufficient rainfall, 1,327.5 h of sunshine, 29% sunshine rate, rainfall mostly concentrated between June and August, with an annual rainfall of 1,200 mm and relative humidity of 80 %.…”
Section: Methodsmentioning
confidence: 99%
“…The TGDR is the largest reservoir in China, located between Jiangjin in Chongqing and Yichang in Hubei, with an area of 349 km 2 . The TGDR implements a hydrological dispatching model of winter storage and summer discharge, creating a hydro-fluctuation zone with a water level difference of up to 30 m during 1 year (Sang et al, 2019 ; Arif et al, 2022b ). The site is part of the subtropical southeast monsoon region's mountainous climate, with an average annual accumulated temperature of 18.2°C, long sunshine hours, sufficient rainfall, 1,327.5 h of sunshine, 29% sunshine rate, rainfall mostly concentrated between June and August, with an annual rainfall of 1,200 mm and relative humidity of 80 %.…”
Section: Methodsmentioning
confidence: 99%
“…Human activities resulting from urbanization and industrialization have deteriorated the riparian zones of many countries [ 1 , 2 , 3 , 4 ]. It is a fact that riparian zones naturally improve water quality since they ensure the safety of both the river and the environment [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rural areas are significantly affected by agricultural activities, while urban areas are significantly impacted by concrete structures [ 22 ]. When researchers compared the correlations between near-field events and far-field events, they found that the correlations between near-field events were stronger, which suggests that the stressor was more concentrated in the near-field events [ 2 , 23 ]. For this reason, it is extremely relevant to investigate how riparian zones respond to different stressors in different river basins.…”
Section: Introductionmentioning
confidence: 99%
“…In some ecosystems, the effects of environmental factors on mass loss impact overrode litter quality itself (Yu et al, 2020). Among them, moisture is one of the important factors affecting material circulation and energy in a riparian ecosystem (Yue et al, 2016;Arif et al, 2022c). It can Frontiers in Environmental Science frontiersin.org indirectly affect the aeration of plant residues, thus affecting their mineralization and decomposition processes (Sun et al, 2012).…”
Section: Discussionmentioning
confidence: 99%